Clinical Utility of Ventricular Repolarization Dispersion for Real‐Time Detection of Non‐ST Elevation Myocardial Infarction in Emergency Departments. Issue 7 (July 2015) - Al‐Zaiti, Salah S.; Callaway, Clifton W.; Kozik, Teri M.; Carey, Mary G.; Pelter, Michele M.
Abstract : Background: A specific electrocardiographic (ECG) marker of ischemia would greatly improve the speed and accuracy of detecting and treating non‐ST elevation myocardial infarction (NSTEMI). We hypothesize that ischemia induces ventricular repolarization dispersion (VRD), altering the T‐wave before any ST segment deviation. We sought to evaluate the clinical utility of VRD to (1) detect NSTEMI cases in the emergency department (ED) and (2) identify NSTEMI cases at high risk for in‐hospital major adverse cardiac events (MACEs). Methods and Results: We continuously recorded 12‐lead Holter ECGs from chest pain patients upon their arrival to the ED. VRD was quantified using principal component analysis of the 12‐lead ECG to compute a T‐wave complexity ratio (ie, ratio of second to first eigenvectors of repolarization). Clinical outcomes were obtained from hospital records. The sample was composed mainly of older males (n=369; ages 63±12 years; 63% males), and 92 (25%) had NSTEMI and 26 (7%) had MACEs. Baseline T‐wave complexity ratio modestly correlated with peak troponin levels ( r =0.41; P <0.001) and was a good classifier of NSTEMI events (area under the curve=0.70). An increased T‐wave complexity ratio on the presenting ECG was strongly associated with NSTEMI (odds ratio [OR]=3.8 [2.1 to 5.8]) and in‐hospital MACE (OR=8.2 [3.1 to 21.5]). Conclusions: A simple measure of global VRD on the presenting 12‐lead ECG correlates with ischemic myocardial injury and can discriminate NSTEMI cases very early during evaluation. Prospective studies should validate these findings and test whether VRD can guide therapy.